2012
DOI: 10.1021/ic3012525
|View full text |Cite
|
Sign up to set email alerts
|

Oligometallic Template Strategy for Synthesis of a Macrocyclic Dimer-Type Octaoxime Ligand for Its Cooperative Complexation

Abstract: The new acyclic tetraoxime ligand H(4)L(1), having two allyl groups at the terminal benzene rings, was designed and synthesized. The ligand H(4)L(1) was converted to five kinds of the trinuclear complexes, [L(1)Zn(3)(OAc)(2)], [L(1)Zn(2)La(OAc)(3)], [L(1)Zn(2)Ca(OAc)(2)], [L(1)Zn(2)Sr(OAc)(2)], and [L(1)Zn(2)Ba(OAc)(2)]. The terminal allyl groups were introduced so that the olefin metathesis could convert the metal complexes into the dimeric macrocyclic ligand H(8)L(3). The X-ray crystallographic analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…Heterometallic coordination polymers containing alkaline earth (AE) metals have attracted increasing attention owing to their fascinating architectures along with their potential applications in the fields of catalysis,1 materials science,2, 3 and biochemistry 4. However, these types of complexes are very scarce and only a limited number of complexes, namely AE‐Zn,5, 6 AE‐Cu,710 AE‐Ni,11, 12 AE‐Co,13 AE‐Fe,14 AE‐Mn,10, 15 and AE‐Ln16–22 have been reported. The inclusion of alkaline earth metals into the heterometallic coordination polymers remains a great challenge for the following two important reasons: 1) the large and variable coordination numbers and versatile coordination behavior of alkaline earth metals make the coordination architectures of the coordination polymers uncontrollable and 2) the alkaline earth metal ions are oxophilic, while the transition metal ions have a strong tendency to coordinate N ‐donors as well as O ‐donors; it is quite possible that the competition reaction between the alkaline earth metals and the transition metals in coordinating to the same ligand gives rise to homometallic coordination polymers rather than heterometallic ones.…”
Section: Introductionmentioning
confidence: 99%
“…Heterometallic coordination polymers containing alkaline earth (AE) metals have attracted increasing attention owing to their fascinating architectures along with their potential applications in the fields of catalysis,1 materials science,2, 3 and biochemistry 4. However, these types of complexes are very scarce and only a limited number of complexes, namely AE‐Zn,5, 6 AE‐Cu,710 AE‐Ni,11, 12 AE‐Co,13 AE‐Fe,14 AE‐Mn,10, 15 and AE‐Ln16–22 have been reported. The inclusion of alkaline earth metals into the heterometallic coordination polymers remains a great challenge for the following two important reasons: 1) the large and variable coordination numbers and versatile coordination behavior of alkaline earth metals make the coordination architectures of the coordination polymers uncontrollable and 2) the alkaline earth metal ions are oxophilic, while the transition metal ions have a strong tendency to coordinate N ‐donors as well as O ‐donors; it is quite possible that the competition reaction between the alkaline earth metals and the transition metals in coordinating to the same ligand gives rise to homometallic coordination polymers rather than heterometallic ones.…”
Section: Introductionmentioning
confidence: 99%
“…We have already demonstrated that a binding selectivity trend of alkali metal << Zn 2+ < alkaline earth < rare earth metal ions was observed in the shorter L 1 Zn2M system [57] and related complexes [79][80][81][82][83] without chiral auxiliary. If the longer L 4 Zn3M system having a chiral auxiliary also shows a similar selectivity trend, Ba 2+ in the L 4 Zn3Ba can be efficiently replaced by La 3+ .…”
Section: Helicity Inversion By Metal Exchangementioning
confidence: 92%
“…The synthetic route to H 4 L is shown in Scheme . The 2,3‐dihydroxynaphthalene‐1,4‐dicarbaldehyde was synthesized by the standard method according to the literature . The 1 H NMR spectrum of the ligand obtained shows clearly that it was highly symmetrical.…”
Section: Methodsmentioning
confidence: 99%
“…The coordination chemistry of transition metal complexes with Salen‐type N 2 O 2 tetradentate ligands (N,N′‐disalicylideneethylenediamine) have achieved a considerable attention in the past decades due to their potential application in catalysts, biological fields, electrochemical conducts, nonlinear optical materials, magnetic materials, luminescence properties and supramolecular architecture . Chemical modifications of substituent or functional groups in the Salen N 2 O 2 ligands are effective in exchanging the structures or the main functions of the complexes, such as Salamo ligand, a Salen's analogue, (R‐CH = N‐O‐(CH) n ‐O‐N = CH‐R) is one of the most versatile ligand . Noticeably, a number of works have been devoted to synthesize and characterize mono‐, di‐ and multinuclear transition metal(II) complexes bearing mono(Salamo)‐type ligand orits derivatives .…”
Section: Introductionmentioning
confidence: 99%